COVID-19 disease treatment: pivotal challenges in the arena of umbilical cord-mesenchymal stem cells (UC-MSCs) - Soliman, Al-Hassan; Abdellatif, Mohamed (Frontiers in Cell and Developmental Biology, 2023)
This century’s first major epidemic of a new coronavirus illness (2019-nCoV) was a tremendous shock to the healthcare system. The onset of the pandemic has caused severe economic and health shortages. At this time, there are no viable treatments for COVID-19. Several clinical studies using cell-based therapies, such as umbilical cord mesenchymal stem cells, have showed promising results (UC-MSCs). UC-MSCs have been the focus of much study because to their potential as a treatment option for COVID-19 patients. Cytokine release syndrome, often called cytokine storm, increases the risk of morbidity and mortality from COVID-19. It has been established that UC-MSCs may suppress and control both the adaptive and innate immune responses by modulating the release of immunostimulatory cytokines. The purpose of this study is to assess and clarify the use of UC-MSCs for the treatment of ARDS caused by COVID-19.